Comparison of two testing strategies for Mycoplasma genitalium in emergency department patients across a statewide health system - Johnson, Emily; Tieman, Molly; Dumkow, Krista; Pavich, Emily (The American journal of emergency medicine, 2024)
Mycoplasma genitalium (Mgen) is a sexually transmitted infection (STI) that has an estimated prevalence in the general population of 2.3% in women and 1.1% in men aged 21–23 years. (Hilbert and Reno, 2018) A cross-sectional study conducted in a community emergency department (ED) determined that the prevalence of Mgen was 14.8% in asymptomatic female patients. (Centers for Disease Control and Prevention (CDC). Sexually Transmitted Infections Treatment Guidelines, 2021) The Centers for Disease Control and Prevention (CDC) 2021 STI Treatment Guidelines recommend testing for Mgen in select circumstances. This study aims to determine what testing strategy in ED patients results in the most appropriate treatment of Mgen based on CDC recommendations. This multicenter, retrospective, pre- and post-intervention cohort study assessed adherence to CDC recommendations for appropriate management of Mgen in ED patients. Inclusion criteria were patients at least 18 years of age discharged from one of the 15 ED sites within the health system studied who were tested for Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis (T. vaginalis), and Mgen. Subjects were excluded if they were pregnant, sexually assaulted, or had indeterminate STI results. For cohort 1, which included patients evaluated from May 2022 through July 2022, Mgen was incorporated into the standard STI testing panel. Cohort 2 consisted of patients evaluated from September 2022 through November 2022; testing for Mgen in cohort 2 was optional, and a testing algorithm based on CDC recommendations was disseminated to ED sites. The primary endpoint was the number of subjects treated appropriately for Mgen in accordance with CDC recommendations. Cohort 1 secondary endpoints included overall prevalence of Mgen in patients who presented to ED sites for STI testing and prevalence in ICD-10 code diagnosed PID. Secondary endpoints for both cohorts included baseline characteristics of patients who tested positive for Mgen. Percent appropriate treatment did not differ significantly between cohort 1 (21%) and cohort 2 (20%), (p > 0.9). However, greater than three times as many subjects were inappropriately treated for Mgen in cohort 1 when the health system studied did not adhere to current CDC Mgen testing recommendations. The overall prevalence of Mgen in ED patients who were tested for STIs was 13.1%. The prevalence of PID ICD-10 diagnosis code in patients positive for Mgen was 2.9%. Based on results of a risk factor analysis to determine if certain baseline characteristics are indicators for a positive infection with Mgen, a positive Mgen result was significantly associated with a positive result for T. vaginalis (p = 0.042). Evidence regarding the preferred testing strategy for Mgen is currently limited. This study demonstrates that testing all STI presenting patients for Mgen results in antibiotic overuse, so adhering to CDC testing recommendations is important. Prevalence of positive Mgen result in ED patients tested for STIs was similar to results of previously published literature. Risk factor analysis results could be used as a screening method to determine what patients should be considered for Mgen testing. Based on the results of this study, we recommend against including Mgen on the standard ED STI testing panel at this time.